2016
DOI: 10.1590/1809-4392201504853
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology of Mouriri guianensis (Melastomataceae) and its interaction with the crepuscular bee Megalopta amoena (Halictidae) in the restinga of Lençóis Maranhenses National Park, Brazil

Abstract: Mouriri guianensis is a Brazilian endemic plant species distributed throughout the Amazon forest, Caatinga, Mata Atlântica and Cerrado domains, extending northward into Venezuela. The aim of this study was to describe the flowering phenology, floral biology and visitors associated with M. guianensis, highlighting the crepuscular bee species Megalopta amoena. Mouriri guianensis flowers from September to March. The flowering, the details of floral biology and the activities of floral visitors were observed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Ours is the first study of Megalopta to analyze data minute by minute and separate observations by flower to explicitly test for overlap, although studies of other Megalopta species show results similar to our Fig. 2 ( Franco and Gimenes 2011 , Krug et al 2015 , Oliveria et al 2016 , Cordeiro et al 2016 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Ours is the first study of Megalopta to analyze data minute by minute and separate observations by flower to explicitly test for overlap, although studies of other Megalopta species show results similar to our Fig. 2 ( Franco and Gimenes 2011 , Krug et al 2015 , Oliveria et al 2016 , Cordeiro et al 2016 ).…”
Section: Discussionsupporting
confidence: 72%
“…Because flowers produced little nectar after midnight ( Kays et al 2012 ), it is unsurprising that overall visitation rates were low in the morning. Other species of flowers that open late at night are visited by Megalopta more frequently in the pre-dawn foraging period ( Roulston 1997 , Franco and Gimenes 2011 , Smith et al 2012 , Krug et al 2015 , Oliveria et al 2016 , Cordeiro et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, only four studies [46][47][48][49] have evaluated the effects of temperature on the activities of nocturnal bees. Two of these studies 46,49 found no effect of temperature, while one study suggests that temperature positively affects bee activity, but only above 25 °C and combined with lower light intensity 47 . The fourth study found that higher temperatures have a moderately negative effect on activity 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, only four studies (Shelly et al 1993, Gottlieb et al 2005, Franco and Gimenes 2011, Oliveira et al 2016 have evaluated in some way how temperature determine nocturnal bees activity. Two of them (Shelly et al 1993, Oliveira et al 2016 have found no effect of temperature, one has implicated that temperature affects positively bee activity over a range of 30°C (Gottlieb et al 2005) and another has found that temperature has a moderate negative effect over activity (Franco and Gimenes 2011). Three of them have also suggested light intensity as a factor affecting bees activity (Shelly et al 1993, Gottlieb et al 2005, Franco and Gimenes 2011).…”
Section: Light Intensity Affects Visitation Rate By Crepuscular Bees mentioning
confidence: 99%